Photo-induced organo-manganese-mediated radical polymerization of acrylates under LED irradiation - Pesqueira, Naralyne M. [UNESP]; Lira, Kathia H. [UNESP]; Bignardi, Camila [UNESP]; da Silva, Milene K. C. [UNESP]; Silva, Thiago F.; Machado, Antonio E. H.; Nascimento, Otaciro R.; Carvalho-Jr, Valdemiro P. [UNESP]; Goi, Beatriz E. [UNESP] (Wiley, 2024)
The role of manganese in photo-induced organometallic-mediated radical polymerization (photo-OMRP) under LED (light-emitting diode) irradiation has not been previously explored. In this study, four manganese (II) complexes, namely [Mn(6-tert-butyl-N,N′-propanebis [salicylimine])] (Mn-Bu), [Mn(6,3-di-tert-butyl-N,N′-propanebis [salicylimine])] (Mn-Bu2), [Mn(6-ethoxy-N,N′-propanebis [salicylimine])] (Mn-Ethoxy), and [Mn(6,3-di-ethoxy-N,N′-propanebis [salicylimine])] (Mn-Ethoxy2), were synthesized using both symmetrical and non-symmetrical tetradentate N2O2 Schiff base ligands. The Schiff base ligands were characterized by Fourier transform infrared spectroscopy (FTIR), ultraviolet–visible spectroscopy (UV–Vis), and nuclear magnetic resonance spectroscopy (NMR). The Mn (II) complexes were characterized by FTIR, UV–Vis, elemental analysis, molar conductivity, cyclic voltammetry, MALDI-TOF mass spectrometry, electron paramagnetic resonance, and rationalized with density functional theory (DFT) studies. All complexes were evaluated as photo-OMRP mediators under LED irradiation at 390 nm and in the 400–800 nm range. The photopolymerization utilized methyl acrylate (MA) and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO) in varying molar ratios of [MA]/[MnII]/[TPO] (900/1/1, 600/1/1, and 600/1/0.5). The photo-OMRP of MA mediated by Mn-Bu2 showed the best control over molecular weight (Mn matching Mn,th) and dispersity (Ð < 1.30) at a [MA]/[MnII]/[TPO] = 600/1/0.5 M ratio. The polymerization system demonstrated a living character, as evidenced by reversible “on/off” light source switching. Furthermore, a block copolymer of poly (methyl acrylate)-b-poly (butyl acrylate) was successfully synthesized employing a sequential visible-light-induced process, with the Mn-Bu2 system showing the best results.
Keywords: copolymerization of MA and nBA; manganese; photo-OMRP; Schiff base